A Barium Titanate‐on‐Oxide Insulator Optoelectronics Platform. Issue 37 (29th July 2021) - Cao, Yu; Tan, Siew Li; Cheung, Eric Jun Hao; Siew, Shawn Yohanes; Li, Changjian; Liu, Yan; Tang, Chi Sin; Lal, Manohar; Chen, Guanyu; Dogheche, Karim; Yang, Ping; Pennycook, Steven; et al.
Abstract: Electro‐optic modulators are among the most important building blocks in optical communication networks. Lithium niobate, for example, has traditionally been widely used to fabricate high‐speed optical modulators due to its large Pockels effect. Another material, barium titanate, nominally has a 50 times stronger r ‐parameter and would ordinarily be a more attractive material choice for such modulators or other applications. In practice, barium titanate thin films for optical waveguide devices are usually grown on magnesium oxide due to its low refractive index, allowing vertical mode confinement. However, the crystal quality is normally degraded. Here, a group of scandate‐based substrates with small lattice mismatch and low refractive index compared to that of barium titanate is identified, thus concurrently satisfying high crystal quality and vertical optical mode confinement. This work provides a platform for nonlinear on‐chip optoelectronics and can be promising for waveguide‐based optical devices such as Mach–Zehnder modulators, wavelength division multiplexing, and quantum optics‐on‐chip. Abstract : A barium‐titanate‐on‐insulator platform with high‐quality barium titanate single‐crystal growth and excellent vertical optical confinement is introduced. The phase‐transition temperature of barium titanate in the platform is extended to at least 700 °C, which helps to avoid difficulties in device fabrication caused by heating, such as cracking. A low propagation loss is verified in the resultant fabricated waveguide.